PERSONAL INCOME TAX ADMINISTRATION IN THE RURAL COMMUNITIES (A STUDY OF SELECTED LOCAL GOVERNMENT AREAS IN OGUN STATE, NIGERIA) - ADEYEYE, Gbadegesin Babatunde; ADEOYE, Adeleke Oluwafemi; ADEYEYE, Adeyemi Mobolaji (Annals of Spiru Haret University. Economic Series, 2018)
The study examined the effectiveness of Personal Income Tax Administration in the rural communities, focusing on assessment and revenue collection methods, effectiveness and efficiency of Relevant Tax Authorities. 125 copies of questionnaire were administered on respondents. Descriptive statistics was used to analyse the opinions of key stakeholders directly connected with Direct and Minimum Tax Assessments in six selected Local Government Areas in Ogun State, Nigeria. Testing of the hypotheses for the study was done using both simple and multiple regression analysis. The findings from the study indicate that tax assessment method significantly encourages voluntary enrolment into the tax net and that effective collection method adopted by the relevant tax authorities ensures optimal tax revenue collection. The study recommends that government should intensify its enlightenment programmes and to introduce awards for recognition of the best rural taxpayers.